Teachers’ Skills Development through Organization of Networking of Inclusive Educational Environment as one of the Pedagogical Conditions of Development of Teachers’ Methodical Competence - Yu. Muller, Olga; D. Rasskazov, Philipp; K. Ilyashenko, Lubov (International Journal of Psychosocial Rehabilitation, 2019)
Development of teachers’ methodical competence in conditions of inclusive education is seen as a conceptual element of designing and effective functioning in a university of inclusive educational environment, that is why one of the pedagogical conditions is the teachers’ active involvement in the work on realization of inclusive educational environment’s networking that allows to solve methodical problems from the perspective of organizers, coordinators, teachers, that provides opportunities to develop skills. The effectiveness of development of teachers’ methodical competence in conditions of inclusive education is ensured through the set of factors, such as active interaction in resource sharing and exchange of professional experience. One of the main component of the process is the social partnership of a university with different organizations and companies that are interested in integration of disabled students into society. For this purpose, the author developed scientific and technical training program within inclusive educational environment “Networking and social partnership”, whose realization is related to creation of collegial support – legislative, organizational and substantive, training, psycho-pedagogical, etc.